Distribution of Glyoxalase-I Polymorphism among Zuni Indians: The Zuni Kidney Project - Degaffe, Guenet H. (2008)
The Zuni Indians are experiencing simultaneous epidemics of type 2 diabetes mellitus (T2DM) and renal disease (Scavini et al., 2003 and Shah et al., 2003). Methylglyoxal, a highly reactive, cytotoxic, cross-linking endogenous aldehyde involved in modification of biological macromolecules, is elevated among patients with T2DM. Glyoxalase-I (Glo1) is the initial enzyme involved in the detoxification of methylglyoxal. Glo1 is a dimeric enzyme with three isoforms, Glo1-1, Glo2-1, and Glo2-2, resulting from a point mutation (A→C) at position 332 of the cDNA. The present study was conducted to explore the hypothesis that specific polymorphisms of Glo1 gene are associated with diabetes and/or albuminuria in Zuni Indians. We studied four groups of Zuni Indians stratified by diabetes status and albuminuria assessed by urinary albumin:creatinine ratio (UACR): Group I: normal controls; Group II: T2DM and UACR <0.03; Group III: T2DM and UACR ≥0.03; and Group IV: non-diabetic participants with UACR ≥ 0.03. Genomic DNA was used as template for PCR amplification of the Glo1 gene. Products were digested to yield 110bp band (homozygous, CC), 54bp and 45bp bands (homozygous, AA), or all three bands (heterozygous, CA). Data on age, gender, UACR, serum creatinine, HbA1c, serum glucose, systolic and diastolic blood pressures and the duration of T2DM among participants in groups II and III were analyzed using analysis of variance. A generalized linear model logistic regression analysis was used to assess the relationships between specific Glo1 polymorphisms to T2DM and UACR. All three Glo1 genotypes were present among the Zuni Indians. There were no significant differences in the distributions of Glo1 genotypes among the study groups (Chi-square, P=0.5590). The prevalence of the Glo1 A allele was higher among diabetic (Groups II and III combined) versus non-diabetic participants (Groups I and IV combined) (Chi-square (p=0.0233). There was an association (Odds Ratio = 2.9, 95% CI 1.3–7.2) between the Glo1 A allele and T2DM.